Long-Term Leukocyte Filtration Should Be Avoided during Extracorporeal Circulation - Jiali Tang; Kaiyu Tao; Jing Zhou; Chongwei Zhang; Lina Gong; Nanfu Luo; Lei Du (Mediators of Inflammation)
Filtration during extracorporeal circulation (ECC) not only removes but also activates leukocytes; therefore, long-term leukocyte filtration may cause adverse effects. In the present study, we tested this hypothesis by priming ECC with 300 mL of canine blood and examining filtration effects in 3 groups (n=6 each) during 60 min ECC. In the control group (Group C) blood was filtrated with an arterial filter for 60 min; in long-term (Group L) and short-term (Group S) groups, blood was filtrated with a leukocyte filter for 60 and 5 min. We found that about 90% of leukocytes were removed after 5 min of filtration in both Groups L and S. Although leukocyte count continued to reduce, mean fluorescent intensities of CD11/CD18, free hemoglobin, and neutrophil elastase increased in Group L and were higher than those in Groups C and S at 60 min. Leukocyte rupture, cytoplasmic leakage, and circulating naked nuclei were also found in Group L. The data support our hypothesis that long-term filtration can induce inflammation and lead to leukocyte destruction.